Сказки дядюшки Иринея: сказки / В. Ф. Одоевский - Одоевский Владимир Федорович (Репро, 1995)
Экземпляры: БС (20170831) / Инвентарный номер: РТШ48783 / Сис.шифр: Р2 / Авт.знак: О-44 / ГРНТИ: 17.82.93 / ББК: 84(2)